O014 Investigating attitudes towards HIV Pre-Exposure Prophylaxis (PrEP). A questionnaire study in men who have sex with men attending sexual health clinics. (30th June 2016) - Bull, Lauren; Dimitrijevic, Pavle; Scarborough, Alexander; Beverley, Sophie; Barber, Tristan; Reeves, Iain; McCormack, Sheena; Rayment, Michael
Abstract : Background/introduction: With the efficacy of HIV pre-exposure prophylaxis (PrEP) proven, provision of PrEP is currently being evaluated by commissioners. The question of who would wish to access PrEP, and where, is important in informing this process. Aim(s)/objectives: To establish potential users' attitudes towards, and experiences of, PrEP. Methods: Ethical approval was obtained to conduct a multi-centre, prospective, anonymised questionnaire study of 1000 HIV negative MSM accessing sexual health clinics. Sexual behaviour, drug use, STI history and previous post exposure prophylaxis (PEP) use were collected. Opinions and attitudes towards PrEP and PrEP availability were assessed. Results: Of 386 analysed questionnaires the majority were British-born (203, 53%), white (300, 78%) men. 345 (89%) reported anal sex within the last month with 168 (43%) and 139 (36%) reporting unprotected insertive and receptive anal intercourse, respectively (103, (26%) and 64, (17%) with multiple partners). 194 (50%) had recently used recreational drugs (within 3 months; 34% "Chemsex" substances). 157 (41%) reported a recent STI (6 months). 223 (58%) reported that they strongly believed they would benefit from PrEP. However, 42/223 (19%) reported no condomless sex. Concerns around taking PrEP were cited by 76 (20%). 167 (43%) expressed a preference for daily PrEP; 139 (38%) for coitally-driven. 311 (80%) supported PrEP delivery by sexual health clinics to MSM, and 233 (60%) to any-one who requests it. 112 (29%) agreed a prescription charge was appropriate. 17 respondents (4%) reported having already taken PrEP: 35% using medication acquired as PEP, and 30% acquiring PrEP privately. 7/17 (41%) reported decreased condom since commencing PrEP. Discussion/conclusion: This comprehensive questionnaire study demonstrates a high willingness to use PrEP in a cohort of at-risk MSM. These data should inform the commissioning process of this efficacious biological intervention.